2020
DOI: 10.1186/s12935-020-01271-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immune-related biomarkers associated with tumorigenesis and prognosis in cutaneous melanoma patients

Abstract: Background: Skin cutaneous melanoma (SKCM) is one of the most malignant and aggressive cancers, causing about 72% of deaths in skin carcinoma. Although extensive study has explored the mechanism of recurrence and metastasis, the tumorigenesis of cutaneous melanoma remains unclear. Exploring the tumorigenesis mechanism may help identify prognostic biomarkers that could serve to guide cancer therapy. Method: Integrative bioinformatics analyses, including GEO database, TCGA database, DAVID, STRING, Metascape, GEP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 42 publications
6
42
0
Order By: Relevance
“…In addition, the expressions of CXCL9, CXCL10, CXCL13, CCL4 and CCL5 were positively correlated with infiltration of six immune cells and 28 types of tumor infiltrating lymphocytes. 12 Our results also showed that CXCL9 and CXCL10 expressed highly, in the lung metastasis microenvironment, Wumei decoction could decrease the expression of both. Wumei decoction, however, whether to reduce the number of tumor cells in the tumor microenvironment also needs further research.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the expressions of CXCL9, CXCL10, CXCL13, CCL4 and CCL5 were positively correlated with infiltration of six immune cells and 28 types of tumor infiltrating lymphocytes. 12 Our results also showed that CXCL9 and CXCL10 expressed highly, in the lung metastasis microenvironment, Wumei decoction could decrease the expression of both. Wumei decoction, however, whether to reduce the number of tumor cells in the tumor microenvironment also needs further research.…”
Section: Discussionsupporting
confidence: 63%
“…Tumor purity was defined as the proportion of malignant cells in tumor tissue, which was closely correlated with prognosis (Yoshihara et al, 2013;Aran et al, 2015;Li et al, 2017). Previously, Hong et al (2020) and Zhang et al (2020) have demonstrated that high immune score and low tumor purity were linked with poor prognosis in osteosarcoma. Therefore, we applied ESTIMATE to determinate the TIME of the two subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The other hub genes were associated with the function of immune, differentiation, proliferation, survival, and apoptosis. Combing with the results of GO and KEGG enrichment, the function of hub genes was centered around B cell function ( Hu et al, 2018 ; Gazon et al, 2018 ; Karin and Razon, 2018 ; Tokunaga et al, 2018 ; Xiao et al, 2019 ; Huang et al, 2020 ; Yang et al, 2020 ). Considering fold change of qPCR was easier to detect in practical production and the gene function of B cell receptor signal pathway, SMC3 , JUN and CXCL10 could be suggested as molecular markers in transportation stress.…”
Section: Discussionmentioning
confidence: 99%